Characterization of the structural response of a lithiated SiO2 / Si interface: A reactive molecular dynamics study. (September 2019) - Verners, O.; Simone, A.
Highlights: Bond degradation mechanisms indicate agreement with bond-strength based estimates. Mechanical failure mechanisms indicate agreement with bond-strength based estimates. Significant effects of Li distribution on mechanical response at interface observed. Abstract: We report the results of a computational study regarding the mechanical properties of a lithiated Si/SiO2 interface using reactive molecular dynamics. The study is motivated by an intended application of SiO2 -coated Si nanotubes as fibers in structural batteries with a fiber-reinforced composite architecture while serving as anodes. According to the results, main failure properties due to partly irreversible bond breakage during mechanical deformation are identified, indicating agreement with bond energy/bond order based estimates. Microscopic failure properties are also identified and interpreted in view of the observed processes of bonding degradation. In particular, the effect of Li distribution on the shear deformation response is evaluated as significant.